(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Detective fiction has been quite prominent in the field of literature. Many writers have been indulged in writing detective stories because of the popularity it holds in its hands. The official arrival of detective fiction has been started by Edgar Allan Poe when he published his story The Murders in the Rue Morgue in 1841 which is considered as an ideal model of detective fiction. The portrayal of place in detective stories plays a vital role as the concept of crime also depends on the place. The selection of place depends on the preference of the writer which would also suit the characters and events of the story. While choosing the place they also consider a place which would increase the charm of the detective as most of the things would be projected by the detective only. Since the detective solves the case, they must know the place in order to understand nature and reason of the crime. Knowing the place also helps them to move ahead in the investigation in a proper manner.